Impact of clonal hematopoiesis of indeterminate potential on arterial atherothrombosis and venous thromboembolism: Protocol for a systematic review and meta-analysis - Angela Todorovski; Tzu-Fei Wang; Evan Sterling; Erin Collins; Marc Carrier; Deborah Siegal; Natasha Kekre; Roy Khalifé; Yan Xu (PLoS ONE, 2025)
Background Clonal hematopoiesis of indeterminate potential (CHIP) is a novel risk factor for thromboembolic events. While CHIP is linked to an increased risk of incident atherothrombosis (ATE), the link between these two conditions varies across studies. Furthermore, the association between CHIP and incident venous thromboembolism (VTE) has not yet been well characterized. Among patients with established ATE and VTE, it is still unclear how CHIP carriership influences their health outcomes. We aim to conduct a systematic review and meta-analysis to: i) determine the impact of CHIP carriership on incident ATE and VTE; and ii) evaluate the prevalence and clinical consequences of CHIP mutations among individuals with established ATE or VTE. Methods We will search MEDLINE, EMBASE, Scopus and CINAHL for randomized trials, cohort studies, or case control studies reporting thromboembolic events among adult CHIP carriers and non-carriers in two populations: i) individuals without prior ATE (coronary artery disease, myocardial infarction, ischemic stroke, peripheral arterial disease) or VTE (pulmonary embolism, deep vein thrombosis, superficial vein thrombosis); and ii) individuals with established ATE or VTE. Cross-sectional studies will be included to determine the prevalence of CHIP among individuals with established thromboembolic disease. The primary outcome will be incident ATE and VTE. Secondary outcomes will be: i) CHIP prevalence among individuals with established ATE or VTE; and ii) recurrent thromboembolism and treatment-associated bleeding among individuals with established ATE or VTE. We will use random-effects meta-analyses, with subgroup analyses by participant demographics, ATE and VTE risk factors, and CHIP-specific characteristics. Discussion By understanding the prognostic impact of CHIP carriership, our findings will inform future research on CHIP’s role as a predictive biomarker for ATE and VTE in the general population and among individuals with established thromboembolic disease. Registration This systematic review protocol was registered with the Internal Prospective Register of Systematic Reviews (PROSPERO, registration number CRD42024539923).